2020
DOI: 10.21203/rs.3.rs-95670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RGD4C Peptide Mediates anti-p21Ras scFv Entry Into Tumor Cells and Produces an Inhibitory Effect on the Human Colon Cancer Cell Line SW480

Abstract: BackgroundAn anti-p21Ras scFv can specifically bind with mutant and wild-type p21Ras but cannot penetrate the cell membrane, which prevents it from binding to p21Ras in the cytoplasm. Here, the RGD4C peptide was used to mediate scFv penetration into tumor cells and produce an inhibitory effect.MethodsRGD4C-linker-EGFP and RGD4C-p21Ras-scFv recombinant expression plasmids were constructed, and the fusion proteins were expressed in E. coli and purified with HisPur Ni-NTA. RGD4C-linker-EFGP was used to test the f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Intrabody was directly injected into the tumor by adenoviral gene transfer. Recently it was shown that the genetic fusion of the RGD4C peptide binding the integrin αvβ3 to the C-terminus of the anti-p21 Ras scFv, which could not penetrate the cell membrane alone, resulted in the penetration and growth inhibition of the human colon cancer cell line SW480 in vitro [87].…”
Section: Krasg12vmentioning
confidence: 99%
“…Intrabody was directly injected into the tumor by adenoviral gene transfer. Recently it was shown that the genetic fusion of the RGD4C peptide binding the integrin αvβ3 to the C-terminus of the anti-p21 Ras scFv, which could not penetrate the cell membrane alone, resulted in the penetration and growth inhibition of the human colon cancer cell line SW480 in vitro [87].…”
Section: Krasg12vmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported a typesetting error. Figures 4 and 5 were transposed.…”
mentioning
confidence: 99%
“…The correct Figs. 4 and 5 are supplied below and the original article [ 1 ] has been corrected.
Fig.
…”
mentioning
confidence: 99%